Chile : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper on Chile seeks to explain why foreign ownership of locally issued sovereign bonds is so low in Chile and its implications. The low foreign ownership seems to be the result of a combination of macroeconomic, regulatory, and technical factors. The Financial Stability Report discusses the issue, and points to the tax on capital gains, costs for custody of securities and other administrative costs, and the relatively small size of the sovereign bond market as the reasons. Our study also finds that a combination of factors contributed to the low foreign ownership, including a moderate supply of sovereign bonds shadowed by strong local demand, illiquid secondary market, tax and administrative burden, the dominance of inflation-indexed bonds, and inconvenience and potential risks associated with foreign exchange transactions. The small size of the market for nominal bonds, the lack of a liquid secondary market, the previous tax regime and existing administrative burden, and transaction costs in the foreign exchange market seem to be the main reasons.